2003
DOI: 10.1128/aem.69.1.644-648.2003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Microorganisms in the Subsurface of the Manus Basin Hydrothermal Vent Field in Papua New Guinea

Abstract: The distribution of microorganisms in the subsurfaces of hydrothermal vents was investigated by using subvent rock core samples. Microbial cells and ATP were detected from cores taken at depths of less than 99.4 and 44.8 m below the seafloor (mbsf), respectively. Cores from various depths were incubated anaerobically with a heterotrophic medium. Growth at 60 and 90°C was ascribed to a Geobacillus sp. in the 448.6-to 99.4-mbsf cores and a Deinococcus sp. in the 64.8-to 128.9-mbsf cores, respectively, based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 28 publications
2
40
0
2
Order By: Relevance
“…In this context, anaerobic and hyperthermophilic Deinococcus sp. have been isolated from the subsurfaces of hydrothermal vents at depths of 64.8 to 128.9 mbsf, where temperatures range from 76 to 91.4°C (Kimura et al, 2003). This finding supports the possibility of the coexistence within the same ecological niche of Deinococcus species and other anaerobic hyperthermophilic archaea.…”
Section: Introductionsupporting
confidence: 76%
“…In this context, anaerobic and hyperthermophilic Deinococcus sp. have been isolated from the subsurfaces of hydrothermal vents at depths of 64.8 to 128.9 mbsf, where temperatures range from 76 to 91.4°C (Kimura et al, 2003). This finding supports the possibility of the coexistence within the same ecological niche of Deinococcus species and other anaerobic hyperthermophilic archaea.…”
Section: Introductionsupporting
confidence: 76%
“…D. radiodurans is dependent on exogenous nicotinic acid because it lacks key enzymes for NAD biosynthesis (637). When a morpholinepropanesulfonic acid (MOPS) Deinococcus radiodurans (14,97,271,325,330) 12.7 (561) Gamma-irradiated canned meat 16 (123) Ground beef and pork, the hides and hair of live beef, creeks Sawdust Air of clean rooms and laboratories of an institute Clothes of people working in an institute Deinococcus radiopugnans (133) 5.3 (133) Haddock tissue Deinococcus radiophilus (1,107,355) Ͼ16 (355) Mumbai duck in India Weathered granite in Antarctica Hypersaline oil-polluted microbial mat in Saudi Arabia Deinococcus proteolyticus (311) 10.3 (561) Feces of a llama Deinococcus grandis (89,478) 11 (89,478) Feces of an elephant 7 (561) Tataouine desert Deinococcus geothermalis (187,299,389,527) 5.1 (187) Hot spring in Italy and Portugal 10 (37°C) (123) Subterranean hot springs in Iceland 16 (50°C) (383) Hydrothermal vents in Papua New Guinea Industrial paper machine water Deinococcus murrayi (187) 9.1 (187) Hot springs in Portugal Deinococcus indicus (595) 4.2 (561) Groundwater in India Deinococcus frigens (254) NA Antarctic soil Deinococcus saxicola (254) NA Antarctic sandstone Deinococcus marmoris (254,591) NA Antarctic marble Surfaces of historic Scottish monuments Deinococcus hohokamensis (501) ND Sonoran desert soil Deinococcus navajonensis (501) ND Deinococcus hopiensis …”
Section: Metabolic Configuration Of D Radioduransmentioning
confidence: 99%
“…These studies found that mesophilic, thermophilic and hyperthermophilic members of Epsilonproteobacteria, Gammaproteobacteria, Aquificales, Thermococcales and Methanococales were the potentially predominant microbial components in the sub-vent biosphere. In addition, previous studies associated with international scientific ocean drilling projects have also indicated the existence of microbial cells in deep subsurface sedimentary and rocky habitats in the hydrothermal vent systems on the Juan de Fuca Ridge (Ocean Drilling Program (ODP) Leg 139 (Cragg and Parkes, 1994) and 169 (Cragg et al, 2000;Summit et al, 2000) and Integrated Ocean Drilling Program (IODP) Expedition 301 (Lever et al, 2013)) and the Manus Basin (ODP Leg 193 (Kimura et al, 2003)). However, these microbial explorations associated with scientific ocean drilling projects have not successfully provided data on the compositions and functions of potential subseafloor microbial communities.…”
Section: Introductionmentioning
confidence: 99%